Assessing OpenStreetMap roads fitness-for-use for disaster risk assessment applications in developing countries: the case of Burundi - Campalani, Piero; Pittore, Massimiliano; Renner, Kathrin (My University, 2022)
Evidence is showing how disasters caused by extreme weather events are surely becoming more frequent at all latitudes, and are definitely representing an ever growing risk in the floods- and landslides-prone territory of Burundi. The still present inequalities of its society and the vulnerable economy make this African country a very relevant and particularly complex case for hazards risk management. A fundamental step in this task is so correctly map the so-called exposure elements to risk, which most notably comprise the population and households, the critical infrastructure, and the transportation network. In relation to this latter exposure element, this article explains in details the analysis that was undertaken in order to estimate the fitness-for-use of the publicly available OpenStreetMap (OSM) roads network database in the context of a recent multi-hazards risk assessment and mapping exercise on behalf of the International Organization for Migration (IOM).
Keywords: fitness-for-use; osm; risk assessment; roads network